Struktur Percakapan Guru dengan Siswa dalam Interaksi Pembelajaran Bahasa Indonesia - Maria Rosalinda Talan (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
The 2013 curriculum is a revision of ideas derived from the previous curriculum where students’ active performance is imposed in study. One of students’ physical activities expected from Indonesian language instruction is speaking or actively involving in class conversation. Therefore, this study aims at describing the structure of teachers and students’ conversation in Indonesian language teaching interaction. This is a descriptive qualitative study. The techniques of data obtaining are recording and taking notes, and the technique of data analysis is heuristic. The result of this study shows the conversation structures in Indonesian language instruction are 1) turn taking occurred when there is a chance to speak. 2) pausing (long and short) occurred since there is no response and when there is hesitation in delivering messages. 3) overlapping occurred since there is a similar utterance or language element produced simultaneously. 4) backchanneling occurred since there are comprehension and acceptance or agreement towards utterances, and 5) adjacency pairs occurred since there are greetings, questions, and requests. Keywords: conversation structure, interaction in teaching